The Role of The Shalawat Al-Kautsar Community in Forming Religious Character Education for Street Children - Fakih Mubarok, Ahmad; Ichsan, Ahmad Shofiyuddin (Mulya Literasi Publishing, 2023)
This research aimed to reveal the role of the Shawalat Al-Kautsar community in shaping religious character education for street children in Wonokromo, Bantul, and Yogyakarta. This research was qualitative research with a case study type. The results showed that the Shalawat Al-Kautsar community had carried out various activities including activities on Islamic holidays, routine studies every Friday night, Wali Songo pilgrimage activities, and hospitality in various regions. The role of the Shawalat Al-Kautsar community was as a center of inspiration, information center, and improvement center. The supporting factors in these activities were the desire to change, adequate educators, and the enthusiasm of the congregation from various regions. While the inhibiting factors were laziness for some members, inadequate budget, and incomplete facilities